Implementation of Animated Video Media in Improving Children's Language Ability - Sunarni, Anik Dwi; Hastuti, Isnaini Budi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to analyze the experiences of teachers and children in utilizing animated videos during the learning process for early childhood education, focusing on their impact on motivation and language development. Methodology: This research employs a qualitative field research approach. Data were collected through interviews, observations, and documentation. The analysis used Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. Results: The findings indicate that animated video media effectively enhance children's motivation and language comprehension. The visual and auditory elements of animated videos contribute to a more engaging and enjoyable learning environment for early childhood learners. Applications/Originality/Value: The study highlights the value of integrating animated videos into early childhood education as a supportive tool for both teachers and learners. It offers practical insights for educators seeking to create fun, effective, and developmentally appropriate learning experiences through multimedia.